1992
DOI: 10.1161/01.hyp.19.6.692
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolism of angiotensin I by neutral endopeptidase (EC 3.4.24.11) in spontaneously hypertensive rats.

Abstract: We investigated the processing enzymes involved in the formation of circulating angiotensin-(l-7) after intravenous administration of angiotensin I to conscious spontaneously hypertensive and Wistar-Kyoto rats. Immunoreactive products, including angiotensin I, angiotensin II, and angiotensin-(l-7), were measured in arterial blood by three specific radioimmunoassays. Angiotensin I infusion (2 nmol) induced a rapid increase in immunoreactive angiotensin II and angiotensin-(l-7). Pretreatment with the angiotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 15 publications
3
113
0
5
Order By: Relevance
“…[25][26][27][28] NEP also contributes to the degradation of extracellular BK (specially when ACE is inhibited). 29 In human cardiac tissue, NEP accounts for nearly 50% of the metabolism of BK.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] NEP also contributes to the degradation of extracellular BK (specially when ACE is inhibited). 29 In human cardiac tissue, NEP accounts for nearly 50% of the metabolism of BK.…”
Section: Discussionmentioning
confidence: 99%
“…3.4.24.26) formed Ang-(1-7) from Ang I in canine brain homogenates 13 and vascular endothelial cells obtained from bovine, human aorta, and umbilical veins. 14 Neutral endopeptidase E.C.3.4.24.11 (neprilysin) was then characterized to process Ang I into Ang-(1-7) in the circulation, 15 whereas, thimet oligo peptidase (E.C. 3.4.24.15) generated Ang-(1-7) from the Ang I substrate in vascular smooth muscle cells.…”
Section: Formation and Functions Of Ang-(1-7)mentioning
confidence: 99%
“…In 1992, studies from our laboratory determined that Ang I serves as a substrate for the enzyme NEP, which produces Ang-(1-7) (Yamamoto et al 1992). Recent studies confirmed that NEP can metabolize Ang I directly into Ang-(1-7), and, furthermore, NEP can act upon Ang II to yield Ang-(1-4) and Ang-(3-4), but not Ang-(1-7) in sheep renal proximal tubular membranes (Shaltout et al 2007).…”
Section: Neprilysin 2411mentioning
confidence: 99%
“…Koida and Walter (1976) discovered that this enzyme cleaved the postproline bond of not only oxytocin and bradykinin, but also Ang II, yielding Ang-(1-7). Later, studies from our laboratory showed that POP can utilize the substrate Ang I to yield Ang-(1-7) in spontaneously hypertensive rats (SHRs) (Yamamoto et al 1992). Kato and colleagues (1980) investigated the tissue and brain distribution of POP and found that POP activity was found in all tissues measured, including, but not limited to the heart, kidney, and lung.…”
Section: Prolyl Oligopeptidase 2126mentioning
confidence: 99%